Cardiovascular outcomes of continuous positive airway pressure therapy for obstructive sleep apnea - BALCAN, MEHMET BARAN (AME PUBL CO, 2018)
Obstructive sleep apnea is a common disorder with increased risk for cardiovascular morbidity and mortality. The first choice of treatment of obstructive sleep apnea is continuous positive airway pressure, which reduces excessive daytime sleepiness and improves quality of life in sleep clinic cohorts. Nevertheless, the majority of patients with cardiovascular disease and concomitant obstructive sleep apnea do not report daytime sleepiness, and adherence to treatment is insufficient particularly in this group. The current article aims to give an updated overview of the impact of continuous positive airway pressure therapy on cardiovascular outcomes mainly based on the observational studies and the recent randomized controlled trials.
Keywords: Obstructive sleep apnea (OSA); cardiovascular outcomes; continuous positive airway pressure (CPAP); randomized controlled trial (RCT); CORONARY-ARTERY-DISEASE; HEART-FAILURE PATIENTS; SHORT-TERM WITHDRAWAL; BLOOD-PRESSURE; RESISTANT HYPERTENSION; ATRIAL-FIBRILLATION; OXIDATIVE STRESS; SYMPATHETIC ACTIVITY; PULMONARY-HYPERTENSION; ENDOTHELIAL FUNCTION